Rehabilitation of Composite Column Subjected to Axial Load - Hassooni, Anas Nahidh; Al-Zaidee, Salah R. (Salehan Institute of Higher Education, 2022)
Concrete Filled Double Steel Tube (CFDST) columns are a modern technique of composite structural element that has fire resistance and has been adopted in high-rise building structures. The Concrete Filled Steel Tube (CFST) columns also have high strength and ductility due to composite action. This type of column CFST can sustain a heavy load with high performance and has been adopted in recent years in many countries around the world. The aim of the present work is to study the behavior and strength of rehabilitation of composite columns that are made from concrete core and surrounded steel tubes under the effect of axial compression loads with different height to diameter ratios such as 5.46, 10.91, and 16.37, respectively, by experimental tests. Double skin methodology is adopted to repair the damaged columns that were tested up to 85% of the ultimate load. Strength column capacity of double skin columns, axial and buckling deformations with axial and buckling strains are investigated. Test results showed that the repaired specimens up to 85% of the ultimate load had the same strength carrying capacity as compared with the control specimens, which had the same geometry. The ductility of an 800 mm specimenâ€™s height is greater than the other tested specimens, while the stiffness of short specimens becomes high.Â Doi: 10.28991/CEJ-2022-08-03-013 Full Text: PDF